Differences in Eating Habits, Lifestyle, and Weight Changes of Indonesian College Students Based on Their Residence During The COVID-19 Pandemic - Dewanti, Lintang Purwara; Sitoayu, Laras; Mardiyah, Sarah; Melani, Vitria (University of Sultan Ageng Tirtayasa, 2022)
The COVID-19 pandemic has indirectly forced people to adapt to the new normal, doing activities outside the home with proper health protocols or not leaving the house to reduce the spread of the virus; this also affects food consumption and sedentary behavior. For some people, the pandemic causes anxiety and even stress. The design of this study was cross cross-sectional, using a survey method online with Google Form carried out from April to September 2021. Descriptive analysis was conducted on 1185 respondents who are currently studying at universities in Indonesia., The results of the study stated that the pandemic had an impact on Indonesian students. This survey researched the differences in eating habits, changes in body weight, and lifestyle in Indonesian students based on where they lived during the Covid-19 pandemic. From the results of data analysis, it is known that most of the respondents experienced changes in body weight during the Covid-19 pandemic, whether they lived together or alone. However, more than half of the respondents have a habit of weighing their body weight irregularly. The results showed that the COVID-19 pandemic influenced eating habits, lifestyle, and changes in body weight. The community, especially students, both living alone (dormitory/boarding/apartments) or living with family or relatives should have sufficient knowledge and attitudes about nutrition to maintain unwanted weight changes during the pandemic.